EDITORIAL - Vargas, J. V. C. (Revista de Engenharia Térmica, 2013)
The problem of sewage and urban solid waste treatment has been increasing exponentially together with population and consumerism growth. There are many environmental questions about sewage and urban solid waste (including hospital waste), mainly when it is considered the fact that not the entire population has access to an adequate treatment system. Even with the current growing stage of development, part of the population does not have basic sanitation and, therefore has their waste disposed inadequately many times in rivers or creeks, and in garbage dumps and landfills. Human wastes are rich in organic material and do not comply with environmental laws standards for disposal in reception venues. In garbage dumps, the leachate that is produced by the urban solid waste degradation contaminates the soil, reaching the groundwater causing several diseases. Besides sewage, there are still other problems resulting from animal protein production, in which the animal confinement produces large amount of residuals with high organic load, causing serious problems when disposed directly in the environment. The thermal engineering community could contribute enormously to the search of solutions through the development of innovative engineering projects for the sewage and urban solid waste treatment, integrated with energy generation systems, contributing to green house gases emission reduction and the valorization of generated subproducts. Integrated complex systems could be conceived from existing technologies currently at an advanced development stage such as: biodigesters, microalgae cultivation photobioreactors, biofuels extraction and production, animal feed and human food supplies production, and electric energy generation. The developed technology, if conceived in modular fashion, would allow for the development of products that could supply a wide spectrum of market activities, either combined or separately, according to the demand.